FORMAT LAYANAN DALAM BIMBINGAN KELOMPOK: Jenis Tema-Tema Pelayanan Bimbingan Kelompok - BAGUS IFTHON GHAZALI (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
The group guidance service format is a framework or structure used by counselors or mentors to provide guidance to a group of individuals in one session or meeting. Group counseling services aim to assist group members in understanding and overcoming the various problems or challenges they face, as well as promoting personal growth and positive development. The service formats in group guidance are (1) classical format, (2) group format, (3) field format, (4) individual format, (5) collaborative format, and (6) distance format. As for the types of methods in the service Group guidance includes: home room programs, study trips, discussion groups, group activities, student unions, sociodrama, psychodrama, and drama teaching.